Efeitos da eletroestimulação neuromuscular de corpo inteiro associada ao exercício dinâmico na composição corporal, na capacidade funcional e variabilidade da frequência cardíaca após a cirurgia bariátrica em indivíduos com obesidade - Ricci, Paula Angélica (Universidade Federal de São Carlos, 2021)
Obesity is considered a chronic disease, with several associated risk factors. Changes in the metabolic and lipid profile, excess body fat and impairments in functional capacity are usually present in obese individuals. Therefore, the functional assessment as well as the effects of rehabilitation interventions can be of special relevance for these patients, especially after surgical interventions. In this context, the first study entitled "Responses of different functional tests in candidates for bariatric surgery and the association with body composition, metabolic and lipid profile" was carried out, which aimed to analyze whether body composition, metabolic and lipid profile influence performance maximal and submaximal of individuals with obesity, as well as investigating the responses of these variables in different functional tests. We evaluated candidates for Roux-en-Y bariatric surgery, men and women, aged between 18 and 50 years, who underwent an incremental treadmill test (ITMT), six-minute walk test (6MWT) and two-minute step test (2MST), in addition to the analysis of body composition, metabolic and lipid profile. We found that changes in body composition and metabolic and lipid profile compromise the functional capacity of these individuals. In addition, the ITMT generated greater metabolic, ventilatory and cardiovascular demand when compared to the 2MST and 6MWT, as well as the 2MST requires greater metabolic and chronotropic demand when compared to the 6MWT. Subsequently, we proposed an intervention protocol for these individuals after bariatric surgery, consisting of whole-body electromyostimulation (WB-EMS) and dynamic exercises. Therefore, the aim of our second study, entitled "Effects of whole-body electromyostimulation associated with dynamic exercise on functional capacity and heart rate variability after bariatric surgery: a randomized, double-blind, sham-controlled study" was to analyze the effects of this intervention performed for six weeks, early, compared to a Sham group, who performed only the dynamic exercises, with the electrical current turned off. In this study, we concluded that the application of WB-EMS was able to reduce body mass index and improve functional capacity, as assessed by the 6MWT, when compared to Sham. However, the WB-EMS did not enhance the effects of exercises on cardiac autonomic modulation. Finally, the third study entitled “Is dynamic exercise associated with whole-body electromyostimulation effective in improving aerobic capacity after bariatric surgery? A randomized, double-blind, sham-controlled clinical trial" aimed to analyze the impact of this same intervention protocol on the aerobic capacity, body composition, anxiety level and sleep quality of these individuals early after bariatric surgery. Finally, we demonstrated that the WB-EMS was able to improve the exercise performance observed by the greater test tolerance (in time, and greater distance covered) in cardiopulmonary exercise test, in addition to demonstrating better responses in blood pressure and lower limb fatigue during test recovery. However, the WB-EMS did not potentiate the effects of exercises in relation to oxygen uptake, body composition, anxiety levels and sleep quality, as both groups showed improvements in these variables.
Effects of whole-body electromyostimulation associated with dynamic exercise on body composition, functional capacity and heart rate variability after bariatric surgery in obese individuals
Keywords: Obesidade; Cirurgia bariátrica; Capacidade funcional; Variabilidade da frequência cardíaca; Exercício dinâmico; Eletroestimulação neuromuscular de corpo inteiro; Obesity; Bariatric surgery; Functional capacity; Heart rate variability; Dynamic exercise; Whole-body electromyostimulation; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA CARDIOVASCULAR; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA